The efficacy of a clustered group-based acceptance and commitment therapy for patients with chronic pain — a randomized controlled semi-crossover trial - Lena Danielsson; Svein Bergvik; Are Hugo Pripp; Gunnvald Kvarstein (Canadian Journal of Pain)
Purpose The efficacy of Acceptance and Commitment Therapy (ACT) for chronic pain when provided as weekly sessions, is well documented. In scarcely populated areas, the traveling distance may be a barrier to weekly attendance. This study aimed to test the efficacy of a group-based ACT intervention, clustered into three bouts of three consecutive days, separated by 4 weeks.Patients and methods A total of 122 patients, recruited from a university hospital pain clinic, were randomized to either a clustered ACT or Treatment As Usual (TAU) provided by the primary health care services. The study had a semi-crossover design. Group effects of ACT versus TAU were assessed 3 months after the start of ACT by using linear mixed models for repeated measures. Outcome measures included pain intensity, health-related quality of life, pain acceptance, catastrophizing, and psychological distress.Results A total of 81 patients completed the ACT intervention. No statistically significant effects were observed on the primary outcome variables, pain intensity and health-related quality of life. Significant group differences in favor of ACT were detected in pain acceptance (modified Cohen`s d = 0.32), including pain willingness (modified Cohen`s d = 0.30) and activity engagement (modified Cohen`s d = 0.23). The treatment effect remained at the 6- and 12-month follow-ups with a trend toward improvement.Conclusion A group-based ACT for chronic pain clustered into 3-day bouts may strengthen pain acceptance processes, including pain willingness and activity engagement. Reasons why the intervention did not affect pain intensity and health-related quality of life are discussed.